Enhancing Literacy and Numeracy: Developing Snakes and Ladders Oriented Toward Higher Order Thinking Skills - Atika Susanti; Abdul Muktadir (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to develop learning media for the snake and ladder game oriented toward higher-order thinking Skills (HOTS) to enhance literacy and numeracy in elementary schools. The method used is Research and Development (R&D) with the ADDIE model. The subjects of this research are fifth-grade students. The instruments include validation sheets for content and design experts and teacher and student response questionnaires. Instrument testing was conducted using a feasibility validity test. Data collection techniques involve document analysis, observation, interviews, questionnaires, and tests. Data analysis was performed using descriptive analysis and descriptive statistics. The results show that the snake and ladder media received a validation score of 0.91 from content experts and 0.93 from design experts. Teacher responses scored 0.94, while student responses reached 0.93, indicating excellent criteria. This media also enhanced students' literacy and numeracy skills, with average scores of 69.22 in Cycle 1 and 85.55 in Cycle 2. Based on these results, improving game features and increasing the variety of HOTS questions is recommended.